Guanxin V Acts as an Antioxidant in Ventricular Remodeling - Liang, Bo; Li, Rui; Liang, Yi; Gu, Ning (Frontiers in Cardiovascular Medicine, 2022)
Background: Our previous studies have shown that Guanxin V (GXV) is safe and effective in the treatment of ventricular remodeling (VR), but its mechanism related to oxidative stress has not been deeply studied. Methods: We applied integrating virtual screening and network pharmacology strategy to firstly obtain the GXV-, VR-, and oxidative stress-related targets, and then highlighted the shared targets. We built the networks and conducted enrichment analysis. Finally, the main results were validated by molecular docking and solid experiments. Results: We obtained 251, 11425, and 9727 GXV-, VR-, and oxidative stress-related targets, respectively. GXV-component-target-VR and protein-protein interaction networks showed the potential mechanism of GXV in the treatment of VR. The following enrichment analysis results gathered many biological processes and “two GXV pathways” of oxidative stress-related to VR. All our main results were validated by molecular docking and solid experiments. Conclusion: GXV could be prescribed for VR through the mechanism, including complex interactions between related components and targets, as predicted by virtual screening and network pharmacology and validated by molecular docking and solid experiments. Our study promotes the explanation of the biological mechanism of GXV for VR.